Biology and Demographic Statistics of Spodoptera frugiperda on Corn (Zea mays L.) and Spinach (Amaranthus hybridus L.) - Rahmawati, Alvina Eka; Rahardjo, Bambang Tri (University of Brawijaya, 2024)
Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) is an invasive pest originally from Central America. The S. frugiperda attack was first documented in Indonesia in 2019. Due to its voracious feeding habits, S. frugiperda can lead to significant losses. This study aims to provide insights into the developmental patterns, births, and deaths of S. frugiperda, utilizing corn as the main host and spinach as an alternative host. The research was conducted at the Pest Laboratory and wire house of Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya from February 2023 to April 2023. This study included two treatments and ten replicates, requiring a total of 500 eggs with 25 individuals for each replicate. The results showed that the survival curve and survival rate of S. frugiperda in both treatments were classified as type I curves. The values of gross reproduction rate (GRR), net reproduction rate (Ro), intrinsic growth (r), and average generation length (T) in corn leaves were 1,280.20; 518.48; 0.27; 30.79, respectively. In contrast, the corresponding values for spinach leaves were 927.09; 322.15; 0.21, 36.23. Based on the biological data and demographic parameters, it can be concluded that spinach plants may serve as viable as alternative hosts for S. frugiperda.